الحكاية الشعبية والطفل - قرفي, السعيد; علال, هدى; كياتي, هدى; لسود, وردة (University of Eloued جامعة الوادي, 2024)
تعد الحكايات الشعبية سلسلة من الوقائع، و الأحداث المتتالية غايتها غرس القيم الدينية والأخلاقية والاجتماعية والنفسية من صدق وشجاعة وصبر واحسان ورحمة لدى الطفل بغية تقويم سلوكه، وتنشئه تنشئة سليمة، فهي تقوم على مجموعة من الآليات الفنية منها السرد والحوار والوصف...كل هذه الأبعاد تلعب دورا كبيرا في تطوير شخصيته ، وإثارة انتباهه، وتنمية قدراته العقلية وتشجيعه على الإبداع والاستماع مما يعزز تركيزه، وقدرته على فهم الأحداث، والتعامل مع التحديات والصراعات المواجهة له كما تطور الملكة اللغوية لديه. Folk tales, a series of interconnected narratives and events, aim to instill in children religious, ethical, social, and psychological values such as honesty, courage, patience, kindness, and compassion. These tales serve as a means of shaping children's behavior and nurturing their sound upbringing. Employing a range of artistic techniques, including narration, dialogue, and description, folk tales play a pivotal role in developing children's personalities, captivating their attention, fostering their cognitive abilities, encouraging creativity, and promoting active listening skills. Consequently, folk tales enhance children's concentration, comprehension of events, and ability to navigate challenges and conflicts. Moreover, they contribute to the development of children's linguistic competence.
دراسة في الأبعاد القيمية والفنية
398/003
Keywords: الحكاية الشعبية- الطفل- القيمية- التربية- الأبعاد الفنية; Folk tales; child; values; education; artistic dimensions